Surface plasmon resonance sensor based on gold-graphene quantum dots thin film as a sensing nanomatrix for phenol detection - Hashim, Hazwani Suhaila; Fen, Yap Wing; Omar, Nur Alia Sheh; Daniyal, Wan Mohd Ebtisyam Mustaqim Mohd; Fauzi, Nurul Illya Muhamad; Abdullah, Jaafar; Mahdi, Mohd Adzir (Elsevier Ltd, 2024)
Surface plasmon resonance sensor has sparked an interest among researchers as it offers a lot of advantages. However, this optical sensor encountered a drawback of poorly sensitive towards low concentration of target analytes. Hence, a modification was done on the gold thin film by incorporating a layer of graphene quantum dots. The sensing performance of the gold and gold-graphene quantum dots thin films was tested for phenol, which is a widely distributed pollutant in the environment. The surface plasmon resonance sensor based on the fabricated gold and gold-graphene quantum dots thin films were successfully carried out over a broad range of phenol from 0.1 to 1000 µM. Comparing the sensing performance of both thin films, lower limit of detection of 0.1 µM was achieved by the gold-graphene quantum dots thin film whereas gold thin film obtained a value of 1 µM. The gold-graphene quantum dots thin film also exhibited a higher sensitivity value of 0.02199° µM−1 for the phenol sensing. The findings provide evidence that the addition of graphene quantum dots to the gold thin film surface has significantly improved the phenol sensing capabilities of this optical sensor. In addition, the changes in the refractive index of the phenol solution as well as the refractive index and thickness of the gold-graphene quantum dots thin film were verified using the fitted SPR curves. The performance of the gold-graphene quantum dots thin film then was further analyzed using full width at half maximum, detection accuracy, and signal-to-noise ratio that demonstrated the potential of this surface plasmon resonance sensor for phenol detection. This gold-graphene quantum dots thin film-based SPR sensor also gave excellent selectivity towards phenol compared to other interfering substances. Additionally, atomic force microscopy proved the interaction between phenol and the thin film as a change in the RMS roughness can be observed.